e g occupancy as an effective descriptor for the catalytic activity of perovskite oxide-based peroxidase mimics - Xiaoyu Wang (Nature Portfolio, 2019)
The search for peroxidase-like as well as other enzyme-like nanozymes mainly relies on trial-and-error strategies, due to the lack of predictive descriptors. Here, the authors fill this gap by investigating the occupancy of e g orbitals as a possible descriptor for the peroxidase-like activity of transition metal oxide nanozymes